The Yoga Directory - Doeser, Linda (Edison Chartwell Books, Inc., 2003)
Explores the underlying philosophy and some of the different yoga paths and techniques as well as ideas on adapting yoga to fit your own lifestyle and to reduce the stresses of everyday life.
Include Color Illustration, Glossary and Index
Keywords: Hatha yoga -- Yoga